Epistatic Interaction Between 5-HT1A and Vascular Endothelial Growth Factor Gene Polymorphisms in the Northern Chinese Han Population With Major Depressive Disorder - Han, Dong; Qiao, Zhengxue; Qi, Dong; Yang, Jiarun; Yang, Xiuxian; Ma, Jingsong; Wang, Lin; Song, Xuejia; Zhao, Erying; Zhang, Jian; Yang, Yanjie; Qiu, Xiaohui (Frontiers in Psychiatry, 2019)
Aims: Serotonin 1A receptor (5-HT1A) and vascular endothelial growth factor (VEGF) are widely expressed in the neurons of the hippocampus, and have significant roles in the pathophysiological processes of major depressive disorders (MDD). The present study was designed to examine 5-HT1A and VEGF gene polymorphisms and whether the gene–gene interaction of 5-HT1A and VEGF gene variants were associated with MDD. Methods: A total of 264 MDD patients and 264 healthy controls were included in the present genetic study. The rs6295, rs1364043 and rs878567 single nucleotide polymorphisms (SNPs) in the 5-HT1A gene and the rs699947, rs833061 and rs2010963 SNPs in the VEGF gene were selected for genotypic analyses. The generalized multifactor dimensionality reduction method was employed to assess their interactions. Results: The genotype distributions of the two genes’ respective SNPs were significantly different between patients and controls for 5-HT1A rs6295 (p = 0.041) and VEGF rs2010963 (p = 0.035); however, no significant allelic variation in 5-HT1A (rs6295, rs1364043 and rs878567) and VEGF (rs699947, rs833061 and rs2010963) were found. The interactions between 5-HT1A (rs6295, rs1364043 and rs878567) and VEGF (rs699947,rs833061 and rs2010963) had a CV consistency of 10/10 and p value of 0.0107, which was considered as the best GMDR model. Conclusions: The interactions between 5-HT1A and VEGF gene polymorphisms may play a key role in the development of MDD in the Northern Chinese Han population.